Pengaruh Tarif Pajak, Keadilan Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor pada Pemerintah Daerah Kota Kupang - Made Denny Oktariyana; Fransiskus Marlon Reu; Olivia Latumahina (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2023)
This research aims to determine the effect of Tariffs, Tax Justice and Tax Sanctions on taxpayer compliance. This research uses a quantitative approach, this research was conducted at the Kupang City Regional Government. The Regional Government of Kupang City has a problem related to the number of motor vehicle tax arrears which is increasing every year, in 2022 it will record arrears of 114,571, namely 44% of the total 258,824 registered vehicles. This is due to a lack of taxpayer awareness which causes regional income revenues to not be absorbed optimally. The sampling method used the incidental sampling method, so that a sample of 100 respondents was obtained. This research data was collected using a questionnaire which was then processed using multiple linear regression analysis tests with the help of SPSS version 22. The results of the research stated that Partial Tax Rates had a positive and significant effect on Motor Vehicle Taxpayer Compliance. Tax rates partially have a positive and significant effect on motor vehicle taxpayer compliance. Tax sanctions partially have a positive and insignificant effect on Motor Vehicle Taxpayer Compliance.